When designing vaccines, consider the starting material: the human B cell repertoire. (August 2018) - Havenar-Daughton, Colin; Abbott, Robert K.; Schief, William R.; Crotty, Shane
Graphical abstract: Highlights: Antigen-specific naive human B cell repertoire analysis as clinical trial prelude. Protein-specific and epitope-specific quantitation of B cells before antigen exposure. B cell precursor frequency and affinity strongly impact germinal center responses. Antigen-specific B cell repertoire study informs immunogen design and prioritization. Abstract : Most viral vaccines provide protection from infection through the generation of neutralizing antibodies (nAbs). The repertoire of B cells responding to immunization is the starting material from which nAbs eventually arise. Immunization strategies are increasingly targeting precise B cell specificities to mimic nAbs generated during natural infection, in an effort to maximize the potency of the vaccine-elicited Ab response. An understanding of the human B cell specificities capable of immunogen recognition can aid in immunogen design and inform decision-making for clinical advancement. Here, we review what is known about antigen-specific and epitope-specific naive B cell repertoires in humans and mice, and we consider the challenges for identifying and analyzing antigen-specific naive B cell repertoires. Finally, we provide a framework for further exploration, interpretation, utilization of the B cell repertoire to facilitate vaccine discovery.